Pengaruh Kinerja Alat Suling Dan Kesesuaian Lahan Terhadap Produksi Minyak Nilam Di Kabupaten Aceh Jaya - Ramayana Ramayana; Widyawati Widyawati (Jurnal Agrisep, 2013)
ABSTRACT. This study aims to analyze the influence of the performance of distillation equipment and suitability of land stills to patchouli oil in Aceh Jaya. The method used is a Latin square design on the basis of the type of production areas, varieties of patchouli and tools of refiners. Performance refinery observed that vary according to the area of production, varieties of patchouli and specification tools refiners. The results showed that the performance optimization of different distillation apparatus according to the specifications of agro-climatic regions of production, varieties and types of equipment refiners. This also causes the variation of performance and patchouli oil refining business profits. Futhermore, appropriate agro-climatic regions and agro-ecological production, the smaller the value of the investment required to achieve optimal distillation process. For areas that are less appropriate in each agro-climate varieties of investment required with a larger value. To obtain better distillation process performance when cultivated varieties according to agro-climatic and agroecology.